Intrapancreatic accessory spleen: an important differential to consider before surgery - U. Contractor, MBBS, MRCS; I. Henderson; A. Zaitoun, MD, PHD, FRCPath (Elsevier, 2014)
Solid tumours in the tail of the pancreas may present a diagnostic dilemma if the clinical history, imaging features or cytology is not conclusive. The common differential diagnoses for a pancreatic tail mass are a primary malignancy, neuroendocrine tumour or a retroperitoneal tumour. However a comparison to the adjacent spleen on imaging may help identify aberrant splenic tissue. We present the case of an incidental finding of a solid tumour in the tail of the pancreas, which was resected and a histological diagnosis of an intrapancreatic spleen (IPAS) was made. A suspicion of IPAS when reviewing the imaging may have prevented the resection of a benign tumour.